Health promoting practices and personal lifestyle behaviors of Brazilian health professionals - Hidalgo, Karen D. (2016)
Background: This study was conducted to examine the lifestyle behaviors and health promoting practices of physicians, nurses, and community health workers in Brazil. Methods: A random sample of primary health care units in Brazil was selected, and a pretested questionnaire was administered via phone interviews, in 2011, to 182 physicians, 347 nurses, and 269 community health workers, totaling 798 health professionals. The total initial sample included 1600 eligible health professionals. Variables measured included physical activity, alcohol intake, hours of sleep, diet, and perceived self-efficacy to provide preventive counseling on related lifestyle behaviors. Results: More than 25 % of physicians, nurses, and community health workers reported eating 0-2 portions of fruits and vegetables per day. In terms of cervical and breast cancer, nurses reported to be 'very prepared' to advise patients on these topics more frequently than physicians. The prevalence of smoking ranged from 4.9 % among nurses to 7.4 % among community health workers. The proportion of physical inactivity ranged from 40. 3 % among nurses to 52.1 % among community health workers. Conclusion: A reasonably high proportion of physicians, nurses, and community health workers report not engaging in healthy lifestyle behaviors that impact chronic diseases, thus, they may be less likely to encourage such behaviors in their patients.